Psychometric Properties of an Instrument to Evaluate the Execution of a Didactic Sequence in Higher Education - Ávila-Camacho, Martha Gabriela; Juárez-Hernández, Luis Gibran (Revista Electrónica Educare, 2023)
Aim. To analyze the psychometric properties of construct validity and reliability of an instrument to assess the didactic sequence. Methodology. The instrument was administered to 488 students enrolled in Bachelor’s Degrees in Preschool and Elementary Education; the students were working on the 2012 study plans. They were informed of the purpose of the research and the confidentiality of the results; they also were asked for their consent to use the data collected. The construct validity analysis implemented a cross-validation process involving an exploratory factor analysis (EFA) and a confirmatory factor analysis (CFA). Reliability was evaluated with Cronbach’s alpha. Results. The EFA revealed the correspondence of the factorial model obtained with the theoretical model, since only one factor was found to explain the 63% of variance, in which all items were represented. The CFA showed the empirical sustainability of the factorial model and optimal fit (Ratio χ2/gl: 2.19; GFI: 0.942; RMSAE: 0.063; RMR: 0.029; CFI: 0.977; TLI: 0.971). The study also confirmed the presence of convergent validity. Finally, the Cronbach’s alpha result was 0.931, indicating optimal reliability. Conclusions. The instrument has adequate psychometric properties. Therefore, its utilization ensures the acquisition of reliable results in the evaluation of didactic sequences in higher education.